Understanding the regulatory-procurement interface for medicines in Africa via publicly available information on standards, implementation, and enforcement in five countries - Jillian C. Kohler; Mariangela Castro-Arteaga; Saher Panjwani; David Mukanga; Murray M. Lumpkin; Bonface Fundafunda; Anthony B. Kapeta; Chimwemwe Chamdimba; Anna S. Y. Wong; Kristin N. Harper; Charles Preston (Journal of Pharmaceutical Policy and Practice)
Background Substandard and falsified medicines in Africa are a major public health concern. Access to quality medical products in African countries is governed in large part by two major entities at the national level: the regulatory authority and the procurement agency. The importance of national regulators in ensuring quality medical products is well known. The interplay between the national regulator and the national procurement agency also has a significant impact on access to quality medicines but is less understood. This study’s aim was to characterise the regulatory-procurement interface – the intersection of decision-making in these two spheres – using publicly available data from five African countries.Methods For the five target countries, we adapted criteria from WHO’s 2018 Pharmaceutical System Transparency and Accountability Assessment Tool to identify key national policies and practices around the nexus of medicines regulation and procurement.Results Though legal and policy frameworks enabling best practices in procurement were often in place, implementation and enforcement of these practices appear to be key areas for strengthening. In addition, we documented a lack of publicly available information related to the role that quality plays in selecting medical products. Finally, none of the five countries have publicly published the results of their selection decisions with key product details, making it difficult to assess whether basic quality standards are being met.Conclusion Based on these findings, one of the most important next steps for improving the effectiveness and transparency of national procurement is for procurement agencies to publish detailed quality selection criteria and an up-to-date list of the medical products they have purchased, with key product information. We hope these findings can help inform the conversation about implementing and enforcing best practices at the regulatory-procurement interface, with the goal of improving access to quality versions of medical products in Africa and globally.